2018
DOI: 10.3233/jad-171157
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow Up of Patients with Mild-to-Moderate Alzheimer’s Disease Treated with Bapineuzumab in a Phase III, Open-Label, Extension Study

Abstract: Infusion of bapineuzumab 0.5 or 1.0 mg/kg every 13 weeks for up to 3 years was generally well tolerated, with a safety and tolerability profile similar to that in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…Two hundred eighty-four relevant studies were screened and assessed for eligibility. After applying inclusion and exclusion criteria (eFigure in the Supplement), 22 publications of RCTs (evidence level 1B), 11 secondary analyses of RCT data (evidence level 2B), and 1 clinical case report (evidence level 4), including in total 15 508 adult patients (7025 men [45.3%] and 8483 women [54.7%]; mean [SD] age, 69.6 [8.3] years), were selected for inclusion. Table 2 summarizes findings of the included RCTs, whereas eTable 1 in the Supplement reports findings from secondary analyses of RCT data and the case report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred eighty-four relevant studies were screened and assessed for eligibility. After applying inclusion and exclusion criteria (eFigure in the Supplement), 22 publications of RCTs (evidence level 1B), 11 secondary analyses of RCT data (evidence level 2B), and 1 clinical case report (evidence level 4), including in total 15 508 adult patients (7025 men [45.3%] and 8483 women [54.7%]; mean [SD] age, 69.6 [8.3] years), were selected for inclusion. Table 2 summarizes findings of the included RCTs, whereas eTable 1 in the Supplement reports findings from secondary analyses of RCT data and the case report.…”
Section: Resultsmentioning
confidence: 99%
“…Amyloid-Related Imaging Abnormalities and β-Amyloid-Targeting Antibodies bapineuzumab) in a phase 1 study 20 revealed instead a better safety profile (Table 2). Due to growing awareness about the need for expertise in ARIA evaluation, during the conduction of phase 3 studies, [21][22][23][24] reporting of safety MRI scans was gradually transferred from local responsibility to central readers (safety read). In a central MRI second review (final read) of the more than 2000 patients who had completed their participation in phase 3 studies, 39 ARIA-E was detected in 13% of patients receiving active treatment.…”
Section: Clinical Review and Education Reviewmentioning
confidence: 99%
“…Solanezumab ( Honig et al, 2018 ; Liu-Seifert, et al, 2018 ), bapineuzumab ( Arai et al, 2016 ; Brody et al, 2016 ; Ivanoiu et al, 2016 ; Vandenberghe et al, 2016 ; Salloway et al, 2018a ; Salloway et al, 2018b ), BAN2401 ( Logovinsky et al, 2016 ), and gantenerumab ( Ostrowitzki et al, 2017 ) are monoclonal anti-Aβ antibodies. In addition to bapineuzumab phase 1 trial results of increasing plasma concentrations of β-amyloid1-40 in patients ( Arai et al, 2016 ), all anti-Aβ antibodies failed in therapeutic efficiency, discouraging further studies.…”
Section: Potential Targets For Drug Designmentioning
confidence: 99%
“…The first studied candidate monoclonal antibody was bapineuzumab, which targets the Aβ N-terminus and possesses a higher affinity for deposited amyloid plaques than soluble Aβ monomers (116,117). However, multiple studies and a meta-analysis conducted by Abushouk et al assessing the potential use of bapineuzumab in the treatment of AD, reported significant association with severe adverse events and no enhancement of cognitive decline, and therefore concluded that bapineuzumab is not recommended for use in the treatment of AD and clinical trials have since then been discontinued (117)(118)(119)(120)(121)(122)(123).…”
Section: Clinical Trialsmentioning
confidence: 99%